A Case of Torsion of the Gallbladder Suspected with SPECT-CT: Review and Recommendations - Eric Bergeron; Etienne Désilets; Xuan Vien Do; Daniel McNamara; Sami Chergui; Michael Bensoussan (Case Reports in Surgery)
Torsion or volvulus of the gallbladder is a rare situation that rapidly progresses to gangrene and linked with a poor prognosis, even death, if unrecognized and untreated. An interesting and rare case of gallbladder volvulus in which diagnosis was obtained by comparing CT images and HIDA scan with SPECT-CT is presented. Relevant literature is reviewed, and recommendations are outlined.